The Role of V-Domain Ig Suppressor of T Cell Activation (VISTA) in Cancer Therapy: Lessons Learned and the Road Ahead - Hosseinkhani, Negar; Derakhshani, Afshin; Shadbad, Mahdi Abdoli; Argentiero, Antonella; Racanelli, Vito; Kazemi, Tohid; Mokhtarzadeh, Ahad; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Immunology, 2021)
Immune checkpoints (ICs) have pivotal roles in regulating immune responses. V-domain immunoglobulin suppressor of T cell activation(VISTA) is a novel inhibitoryICs, which can be expressed on myeloid cells, lymphoid cells, and tumoral cells.Thus, this IC has a critical role in regulating innate and adaptive anti-tumoral immune responses. Growing evidence has shown that VISTA is one of the main culprits in attenuating anti-tumoral immune responses following IC-based immunotherapy. This review aimed tosummarizethe current knowledge about its structure, its expression phenotype andhighlight its function in the tumor microenvironment (TME) of various cancers.Based on the recent pre-clinical and clinical findings, this review intended to propose a strategy to overcome the immune-resistant state of cancers following conventional IC-based immunotherapy.